The intricate nature of senescence in development and cell plasticity. (December 2022) - Gal, Hilah; Majewska, Julia; Krizhanovsky, Valery
Abstract: Cellular senescence, a stable form of cell cycle arrest, accompanied by pronounced secretory activity, has functional roles in both physiological and pathological conditions. Although senescence has been linked for a long time with cancer and ageing, recent studies have revealed a functional role of senescence in development, regeneration and reprogramming. Notably, the transient presence of senescent cells may be beneficial, in contrast to the potential deleterious effects of persistent senescence in aged or chronically damaged tissues. We will discuss how senescence contributes to embryonic development, cell plasticity and tissue regeneration, as a highly coordinated and programmed cellular state.